Auditory evoked response to an oddball paradigm in children wearing cochlear implants. (May 2023) - Deroche, Mickael L.D.; Wolfe, Jace; Neumann, Sara; Manning, Jacy; Towler, William; Alemi, Razieh; Bien, Alexander G.; Koirala, Nabin; Hanna, Lindsay; Henry, Lauren; Gracco, Vincent L.
Highlights: For children with cochlear implants, language and literacy outcomes remain highly variable, despite early implantation. Cortical auditory evoked potentials in a short oddball paradigm (applicable to the clinic) may help explain this variability. MMN and P3 had lower amplitudes in implanted children with poor outcomes, and P3 was particularly promising as a predictor. Abstract: Objective: Although children with cochlear implants (CI) achieve remarkable success with their device, considerable variability remains in individual outcomes. Here, we explored whether auditory evoked potentials recorded during an oddball paradigm could provide useful markers of auditory processing in this pediatric population. Methods: High-density electroencephalography (EEG) was recorded in 75 children listening to standard and odd noise stimuli: 25 had normal hearing (NH) and 50 wore a CI, divided between high language (HL) and low language (LL) abilities. Three metrics were extracted: the first negative and second positive components of the standard waveform (N1-P2 complex) close to the vertex, the mismatch negativity (MMN) around Fz and the late positive component (P3) around Pz of the difference waveform. Results: While children with CIs generally exhibited a well-formed N1-P2 complex, those with language delays typically lacked reliable MMN and P3 components. But many children with CIs with age-appropriate skills showed MMN and P3 responses similar to those of NH children. Moreover, larger and earlier P3 (but not MMN) was linked to better literacy skills. Conclusions: Auditory evoked responses differentiated children with CIs based on their good or poor skills with language and literacy. Significance: This short paradigm could eventually serve as a clinical tool for tracking the developmental outcomes of implanted children.